Blood flow restriction training promotes functional recovery of knee joint in patients after arthroscopic partial meniscectomy: A randomized clinical trial - Ke, Junjie; Zhou, Xuchang; Yang, Yajing; Shen, Hai; Luo, Xiaobing; Liu, Hui; Gao, Lu; He, Xin; Zhang, Xin (Frontiers in Physiology, 2022)
Purpose To explore the effect of blood flow restriction training (BFRT) on the recovery of knee function in patients after arthroscopic partial meniscectomy (APM). Methods Forty patients undergoing APM surgery were included in this parallel group, two-arm, single-assessor blinded, randomized clinical trial. The subjects were randomly divided into two groups: routine rehabilitation group (RR Group, n=20) and routine rehabilitation + blood flow re-striction training group (RR + BFRT Group, n=20). One subject in each group dropped out during the experiment. All patients received 8 weeks of routine rehabilitation starting from the second day after APM. In addition, patients in the RR + BFRT group required additional BFRT twice a week. Visual analogue scale (VAS) score, range of motion (ROM), one-leg standing test (OLST) score, Lysholm knee score, quadriceps muscle strength, quadriceps thickness, and thigh circumference were evaluated at preoperative, postoperative, 4 weeks and 8 weeks after surgery. Results There were no significant differences in VAS score, ROM, OLST score, Lysholm knee score, quadriceps muscle strength, quadriceps thickness, and thigh circumference between the two groups before surgery (P>0.05). Com-pared with postoperative, VAS score, ROM, OLST score, Lysholm knee score, and thigh circumference were significantly improved in the RR + BFRT group (P<0.05), while quadriceps muscle strength and quadriceps thickness were not significantly enhanced at 8w postoperatively (P>0.05). However, VAS score, ROM, OLST score, Lysholm knee score, quadriceps muscle strength, quadriceps thickness, and thigh circumference were all significantly improved in the RR + BFRT group at 8w postoperatively (P<0.05). Furthermore, compared with the RR group, the above indicators in the RR + BFRT group were significantly improved at 4w and 8w postoperatively (P<0.05). Conclusions BFRT combined with routine rehabilitation training can better promote the recovery of knee joint function in patients after APM, especially the improvement of quadriceps muscle strength and thickness.